Anomalies of Imagination, Self-Disorders, and Schizophrenia Spectrum Psychopathology: A Network Analysis - Rasmussen, Andreas Rosén; Raballo, Andrea; Preti, Antonio; Sæbye, Ditte; Parnas, Josef (Frontiers in Psychiatry, 2022)
Background Anomalies of imagination encompass disturbances of the basic experiential structure of fantasies and imagery that can be explored in a semi-structured way with the Examination of Anomalous Fantasy and Imagination (EAFI). We aimed (1) to examine the distribution of anomalies of imagination among different diagnostic groups and a group of healthy controls, and (2) to examine their relation with disorders of basic self, perceptual disturbances and canonical state psychopathology of the schizophrenia-spectrum (positive, negative and general symptoms). Methods The 81 participants included patients with schizophrenia or other non-affective psychosis (N=32), schizotypal personality disorder (N=15) or other mental illness (N=16) and healthy controls (N=18). The assessment encompassed EAFI, Examination of Anomalous Self-Experience (EASE), parts of Bonn Scale for the Assessment of Basic Symptoms (BSABS) and Positive and Negative Syndrome Scale (PANSS). For network analysis, the associations of EAFI with the other psychopathological variables were tested by Pearson’s correlation coefficient and graphically represented using multidimensional clustering. Comparisons between correlations in the network were tested with Steiger’s test. Results Anomalies of imagination aggregated significantly in schizophrenia-spectrum disorders compared to other mental illness and healthy controls with no difference between schizophrenia and schizotypal disorder. In the network analysis, anomalies of imagination were closely inter-connected with self-disorders. Although, the anomalies of imagination correlated moderately with perceptual disturbance and positive, negative and general state symptomatology, these dimensions aggregated separately and relatively distant in the network. Conclusions The results support that anomalies of imagination are highly characteristic of schizophrenia-spectrum disorders and closely related to self-disorders.